Padronização da quantificação de violaceína produzida por Chromobacterium violaceum através de métodos colorimétricos - Casagrande, Camila (2022)
The Quorum Sensing (QS) regulation is closely related to the biofilm formation mechanism in several microrganisms. In the Chromobacterium violaceum (CV) species it is possible to verify this regulation through the production of violacein, a violet colored pigment. The blocking of the production of this protein has been used as an indicator of QS inhibition. To demonstrate QS inhibition there is no need to disable the bacteria, that is, there is no need for bacterial death. However, quantification of violacein requires robust and laborious laboratory instrumentation, in addition to a demanding costly infrastructure and specialized human resources. In this context, we aimed to evaluate the production and inhibition of violacein, where the readings were performed through the Android application Photometrix UVC coupled to an endoscopic USB camera. To evaluate the blockage of violacein production, it was used salicylic acid, a product of natural origin, widely used as an analgesic, anti-inflammatory and antifebrile. The ideal conditions for C. Violaceum growth and pigment production were also standardized. The microrganism showed better growth and violacein production, when cultivated in Brain Heart Infusion (BHI) culture medium for 24h at 37°C. The minimum inhibitory (125 μg/ml) and bactericidal (2000 μg/ml) concentrations of salicylic acid against CV were established. The salicylic acid at sub-inhibitory concentrations was able to inhibit violacein production and the results of the traditional method of reading were compared with those performed by the Android PhotoMetrix application. The results obtained demonstrate that there is no significant difference between the reading methods, indicating that these technologies can be great allies in research, and can be widely used as a screening method, favoring the discovery of new substances with potent QS inhibition activity and antibiofilms.